2013
DOI: 10.1007/s00221-012-3391-2
|View full text |Cite
|
Sign up to set email alerts
|

Features of cortical neuroplasticity associated with multidirectional novel motor skill training: a TMS mapping study

Abstract: Given the evidence that the primary motor cortex (MI) consists of subpopulations of upper motor neurons tuned to different directional parameters of a motor movement, this study hypothesized that novel motor skill training involving either a bidirectional or more complex multidirectional tongue-typing movement should produce distinct training-related features of tongue MI neuroplasticity in humans. Novel motor skill training consisted of tongue typing using custom-made intra-oral keypads for 30-min over two co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
23
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 49 publications
5
23
0
Order By: Relevance
“…To investigate cortico-cortical interactions between these areas, we measured coherence of spiking and local field potentials (LFPs) recorded simultaneously from MIo and SIo of the left hemisphere as monkeys learned a simple and controlled tongue protrusion task. Several studies using this behavioral paradigm have reported neuroplasticity and modulation of neuronal activity related to tongue protrusion separately in MIo and SIo (13)(14)(15)(16)(17). Here, we show that interactions between MIo and SIo involve coherent networks at multiple frequencies.…”
supporting
confidence: 62%
See 1 more Smart Citation
“…To investigate cortico-cortical interactions between these areas, we measured coherence of spiking and local field potentials (LFPs) recorded simultaneously from MIo and SIo of the left hemisphere as monkeys learned a simple and controlled tongue protrusion task. Several studies using this behavioral paradigm have reported neuroplasticity and modulation of neuronal activity related to tongue protrusion separately in MIo and SIo (13)(14)(15)(16)(17). Here, we show that interactions between MIo and SIo involve coherent networks at multiple frequencies.…”
supporting
confidence: 62%
“…2A) These measures of coherence are presumed to represent the correlation of the outputs from both areas (MS) and the correlation of the outputs from one area with the inputs in the other (MSf and SMf). For each of the 5 sampled training days, D1-D5, we estimated coherence by using a 0.5-s sliding window with 0.01-s steps to show a time-resolved coherence profile in the theta (2-6 Hz), alpha (6-13 Hz), beta (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), and gamma (30-50 Hz) bands. Coherence in these frequency bands is believed to play a role in attention, memory, motor control, and plasticity (16,(18)(19)(20).…”
Section: Resultsmentioning
confidence: 99%
“…Visual attention toward the limb during training also appears to be an important factor for modulating the magnitude and duration of analgesia. 224 It is known that attention and task complexity enhance neural plasticity during motor learning 226,227 and it is apparent that this also applies to neuroplastic changes in the sensory system during sensory training. Clinically, this would mean that progressively graded sensory discrimination training that requires the patient's attention would be most beneficial.…”
Section: A Sensory Trainingmentioning
confidence: 99%
“…Several techniques can help to activate an inactive muscle. First, motor learning induces neuroplastic changes within the brain (Boudreau et al, 2013). Exercises that focus on activation of the ECRB muscle whilst limiting activation of EDC might prove beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…cerebral cortex) to change as a result of internal and external stimuli and changes in behaviour, environment, and emotions (Pascual-Leone et al, 2011). Although pain is a strong driver of neuroplasticity (Coderre, Katz, Vaccarino, & Melzack, 1993), neuroplastic changes can be motivated by motor learning/training (Boudreau et al, 2013). Less discrete cortical organisation might be related to less individualised control of muscles and/or a simplified motor control in chronic pain conditions.…”
Section: Motor Control Differences As a Consequence Of Lateral Epiconmentioning
confidence: 99%